Soviet foreign aid - Goldman, Marshall I. (New York, Praeger, 1967)
This is a study of Soviet Russia's economic relations with her satellites, and other developing countries, since the Second World War. It concentrates on the goals pursued by Russia in foreign aid and trade, her accomplishments and failures in these areas, and the lessons that the West can learn from the Soviet experience. The book is composed of case studies, with chapters on Soviet aid to regions: East Europe, Asia, the Middle East, Latin America, and Africa; and to individual states: the United Arab Republic, India, Afghanistan, and Indonesia.
Includes bibliographical references: p. 254-258.
lje 04/10/2018
Loans
Keywords: Economic assistance; Foreign aid; Soviet Union